The effect of the E484K mutation of SARS-CoV-2 on the neutralizing activity of antibodies from BNT162b2 vaccinated individuals. Issue 13 (18th March 2022) - Uwamino, Yoshifumi; Yokoyama, Takashi; Shimura, Takako; Nishimura, Tomoyasu; Sato, Yasunori; Wakui, Masatoshi; Kosaki, Kenjiro; Hasegawa, Naoki; Murata, Mitsuru
Highlights: Neutralization antibody were measured against SARS-CoV-2 variants after vaccination. Low neutralization antibody titer was observed against beta and delta variants. Neutralization antibody titer against R.1 lineage was equivalent to original Wuhan. The weakened humoral response might not be caused solely by the E484K mutation. Abstract: The reduced vaccine efficacy against the SARS-CoV-2 variant lineage B. 1.351 (beta variant) containing the E484K and N501Y mutations is well known. The E484K mutation in SARS-CoV-2 is thought to be responsible for weakened humoral immunity. Vaccine efficacy against the R.1 lineage, which contains the E484K mutation but not the N501Y mutation, is uncertain. Serum samples were collected from 100 healthy Japanese participants three weeks after receiving the second dose of the BNT162b2 vaccine, and serum neutralization antibody titers were measured against five SARS-CoV-2 variants. The geometric mean neutralization titers measured for the original and R.1 lineages were equivalent (91.90 ± 2.40 and 102.67 ± 2.28, respectively), whereas a low titer was measured for the beta variant (18.03 ± 1.92). Although further investigations with other variant strains and serum samples are essential, our results imply that the weakened humoral response is not caused solely by the E484K mutation. (UMIN000043340).